Treatment of Colle's Fracture with Wrist Immobilization in Palmar flexed & Dorsiflexed Position - Sohail Iqbal Shaikh, Abdul Basit, Javed Iqbal, Saba Sohail Shaikh, Imran Sohail Shaikh (Journal of Islamic International Medical College, 2012)
Objective: To evaluate and compare the radiological and functional results of immobilization of Colle's fracture treated conservatively in two different positions of wrist i.e. palmarflexion(PF) &dorsiflexion (DF).